A Review of Churg–Strauss syndrome (CSS) - Thanga kokila. M,; Venkateshan N,; Gowsalya M,; Maha Lakshmi B,; Jedlin L. J,; Jeya priya M,; Devadhashini G,; Ramya S,; Roshini P,; Subhiksha T, (The Bioscan, 2025)
Churg–Strauss syndrome (CSS) is a rare systemic vasculitis of the small and medium sized blood vessels. The triad of asthma, sinusitis and hypereosinophilia is characteristic of CSS. However, it can affect any organ system with predominance for the skin, respiratory, neurological, gastrointestinal and cardiovascular systems. The natural history of the condition has been described in three phases: prodromal, eosinophilic and vasculitic. Diffuse organ involvement of Churg-Strauss syndrome, especially cardiovascular and rare involvement of the CNS and renal system, suggests a poorer prognosis than usual, and can be fatal. The cause of Churg-Strauss syndrome is unknown, but its characteristic histological findings and association with asthma distinguish it from other vasculitides. Such classification criteria can assist in making the diagnosis of CSS and differentiating the condition from other diseases that cause pulmonary infiltrates with eosinophilia including allergic bronchopulmonary aspergillosis, acute and chronic eosinophilic pneumonia, idiopathic hypereosinophilic syndrome, certain parasitic infections and drug reactions. The treatment of patients with CSS must be tailored to individual patients according to the presence of poor prognostic factors. A combination of high-dose corticosteroids and cyclophosphamide is still the gold standard for the treatment of severe cases, but the use of biological agents such as rituximab or mepolizumab seems to be a promising therapeutic alternative.